EFEKTIVITAS AIR JERUK NIPIS (Citrus aurantifolia) SEBAGAI PENGGANTI CUKA DAN PEMBERI AROMA TERHADAP KUALITAS NATA DE SOYA DALAM PENGEMBANGAN MODUL MATERI BIOTEKNOLOGI SMA KELAS XII - Julia Riska; Darmawati '; Yustina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the effectiveness of lime juice (Citrus aurantifolia) as a substitute for vinegar and flavor concentrates on the quality of nata de soya and develop learning modules nata de soya by administering lime juice (Citrus aurantifolia) on the matter of biotechnology high school class XII. This study consisted of two phases: the first making of Nata de Soya using the experimental method completely randomized design (CRD) consisting of 4 treatments and 3 replications. Parameters measured were thickness, fiber content, acidity (pH) and organoleptic test. The results obtained were analyzed by ANOVA and a further test DMRT at 5% level. The second phase is the phase of development of this learning module consists of three stages, namely Analysis, Design and Development. The results show that lime water provides significant effect on the thickness, fiber content, acidity (pH) and organoleptic test. The best treatment is the treatment concentration of lime juice 2% which resulted in the thickness of 0,93cm, crude fiber content of 1.98%, acidity (pH) of 4.42 and organoleptic texture, color, and the best level of preference. The results of the research development Learning Module on the subjects of biology biotechnology materials high school class XII is very valid.